Association of interpregnancy interval with adverse pregnancy outcomes according to the outcomes of the preceding pregnancy: a longitudinal study with 4.7 million live births from BrazilResearch in context - João Guilherme G. Tedde; Thiago Cerqueira-Silva; Sidney A. Lagrosa Garcia; Brenda V. Amira; Laura C. Rodrigues; Mauricio L. Barreto; Aline S. Rocha; Rita de Cássia Ribeiro-Silva; Ila R. Falcão; Enny S. Paixao (Elsevier, 2024)
Summary: Background: Earlier studies have proposed a link between the Interpregnancy Interval (IPI) and unfavorable birth outcomes. However, it remains unclear if the outcomes of previous births could affect this relationship. We aimed to investigate whether the occurrence of adverse outcomes-small for gestational age (SGA), preterm birth (PTB), and low birth weight (LBW)-at the immediately preceding pregnancy could alter the association between IPI and the same outcomes at the subsequent pregnancy. Methods: We used a population-based linked cohort from Brazil (2001-2015). IPI was measured as the difference, in months, between the preceding birth and subsequent conception. Outcomes included SGA (<10th birthweight percentile for gestational age and sex), LBW (<2500 g), and PTB (gestational age <37 weeks). We calculated risk ratios (RRs), using the IPI of 18-22 months as the reference IPI category, we also stratified by the number of adverse birth outcomes at the preceding pregnancy. Findings: Among 4,788,279 births from 3,804,152 mothers, absolute risks for subsequent SGA, PTB, and LBW were higher for women with more adverse outcomes in the preceding delivery. The RR of SGA and LBW for IPIs <6 months were greater for women without previous adverse outcomes (SGA: 1.44 [95% Confidence Interval (CI): 1.41-1.46]; LBW: 1.49 [1.45-1.52]) compared to those with three previous adverse outcomes (SGA: 1.20 [1.10-1.29]; LBW: 1.24 [1.15-1.33]). IPIs ≥120 months were associated with greater increases in risk for LBW and PTB among women without previous birth outcomes (LBW: 1.59; [1.53-1.65]; PTB: 2.45 [2.39-2.52]) compared to women with three adverse outcomes at the index birth (LBW: 0.92 [0.78-1.06]; PTB: 1.66 [1.44-1.88]). Interpretation: Our study suggests that women with prior adverse outcomes may have higher risks for adverse birth outcomes in subsequent pregnancies. However, risk changes due to differences in IPI length seem to have a lesser impact compared to women without a prior event. Considering maternal obstetric history is essential in birth spacing counseling. Funding: Wellcome Trust 225925/Z/22/Z.